Optogenetically evoked gamma oscillations are disturbed by cocaine administration - Dilgen, Jonathan E.; Tompa, Tamas; Saggu, Shalini; Naselaris, Thomas D.; Lavin, Antonieta (Frontiers in Cellular Neuroscience, 2013)
Drugs of abuse have enormous societal impact by degrading the cognitive abilities, emotional state and social behavior of addicted individuals. Among other events involved in the addiction cycle, the study of a single exposure to cocaine, and the contribution of the effects of that event to the continuous and further use of drugs of abuse are fundamental. Gamma oscillations are thought to be important neural correlates of cognitive processing in the prefrontal cortex (PFC) which include decision making, set shifting and working memory. It follows that cocaine exposure might modulate gamma oscillations, which could result in reduced cognitive ability. Parvalbumin-positive fast-spiking interneurons play an orchestrating role in gamma oscillation induction and it has been shown recently that gamma oscillations can be induced in an anesthetized animal using optogenetic techniques. We use a knock-in mouse model together with optogenetics and in vivo electrophysiology to study the effects of acute cocaine on PFC gamma oscillation as a step toward understanding the cortical changes that may underlie continuous use of stimulants. Our results show that acute cocaine administration increases entrainment of the gamma oscillation to the optogentically induced driving frequency. Our results also suggest that this modulation of gamma oscillations is driven trough activation of DAD1 receptors. The acute cocaine-mediated changes in mPFC may underlie the enhancement of attention and awareness commonly reported by cocaine users and may contribute to the further use and abuse of psychostimulants.